Living under siege : women's narratives of psychological violence within coercively controlling intimate partner relationships : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Psychology at Massey University, Manawatū, New Zealand - Hancock, Carmel M (Massey University, 2017)
As a global epidemic, the violence of women enacted through gendered social power relations of inequality, exploit, harm, and silence women. Specifically, intimate partner violence (IPV) constitutes a systematic pattern of coercive control, embedded within psychological, physical, and/or sexual violence, that intimidates and hurts women through fear and terror. Although previous literature has identified the debilitating effects of psychological violence, within our socio-political landscape physical violence continues to occupy a more visible and privileged position, minimising other forms of violence. The aim of this research, therefore, was to explore and make visible heterosexual women’s experiences of psychological violence within previous intimate relationships, framed through coercive control, to enable a greater understanding of how women become subjected to men’s coercion and control within intimate relationships. The aim was also to explore how psychological violence positions women within the gendered social hierarchy. A narrativediscursive approach analysed the stories of six women subjected to psychological violence and attended to the discursive resources the women used to narrate their experiences. The analysis identified how the women’s experiences of heteronormative coupledom developed into relationships of coercion and control, emphasising their inequitable and subordinate positions within femininity. Becoming entrapped within a destructive pattern of coercion, the women’s everyday lives were micro-regulated through their partners’ tactics of intimidation, isolation, and control and through their own operations of imperceptible disciplinary power. Importantly, the analysis identified particular turning points of resistance enabling the women to leave their relationships, however, they continue(d) to live under siege post-separation, subjected to psychological violence by their ex-partners through the men’s use of both their children and the legal system. The analysis ends with the women’s reflections on how these previous relationships continue to currently affect them.
Keywords: Intimate partner violence; Man-woman relationships; New Zealand; Research Subject Categories::SOCIAL SCIENCES::Social sciences::Psychology